Analisis Komposisi Musik â€œKuasa Tanahâ€ - I Putu Adi Septa Suweca Putra (Journal of Music Science, Technology, and Industry, 2019)
This paper aims to explore and understand more deeply about the music of â€œKuasa Tanahâ€ (or the power of land) composed by a Balinese musician named Dewa Ketut Alit which covertly instills intellectual value in the process of its manifestation. Broadly speaking, each composer certainly has his own method for realizing his work. The difference in methods and forms of the work produced can also provide distinctive characteristics for each composer. This article is more referring to musicality problems that occur in â€œKuasa Tanahâ€ The issue of musicality is very important to understand and peel to see music in a textual manner. Through this issue, in the next turn, it can be used as knowledge and scientific foundation in making another new work, and is expected to open a societyâ€™s perspective so that music is not only regarded as merely entertainment. Using qualitative method through interview and transcription done, in the analysis is fount that in â€œKuasa Tanahâ€, there is a renewal of the packaging system that is reflected in the way the composer works in processing the selected musical elements. The entire work uses several types of local instruments found in Balinese gamelan. Although it uses several instruments from Balinese gamelan, but the music produced is sounded universal. This shows that the gamelan will elegantly coexist above equality and surge as independent music amidst the infinite dynamics of global music. Keywords: musical work, â€œKuasa Tanahâ€, newness, local, global.